(untitled) (INNOTEC, 2016)
The Cryptosporidium genus is composed of protozoan parasites that infect the epithelial cells of the gastrointestinal tract of a wide range of vertebrates. This parasitosis can be transmitted through routes that include the direct contact with infected animals or persons as well as through the ingestion of food or water containing the environmental stage of this microorganism, the oocysts. The sanitary and environmental significance of this parasite makes necessary for our country to implement specific, fast and robust tools enabling a proper study of their clinical impact as well as its environmental distribution (temporal and geographical). This paper describes the implementation of molecular and microscopy methods that will contribute to the understanding of the clinical incidence and environmental distribution of these protozoa as well as to the mitigation of the risk that Cryptosporidium potentially represents in our country.